2018
DOI: 10.1111/jpc.14078
|View full text |Cite
|
Sign up to set email alerts
|

Trends in late‐onset sepsis in a neonatal intensive care unit following implementation of infection control bundle: A 15‐year audit

Abstract: Multifaceted infection control bundle practices with a concerted team effort in the implementation, with continuing education, feedback and reinforcement of best infection control practices, can sustain the gains achieved by infection control for a long period of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Important outcome measures include mortality, readmission, patient and family experience, and staff outcomes. Outcome measures in ICUs include mortality, outcomes of infection control, prevention of gastrointestinal bleeding and pressure ulcers, prevalence of sepsis, central line‐associated bloodstream infections (Lee et al., 2019; Pharande et al., 2018), ventilator‐acquired pneumonia (VAP) and catheter‐related bloodstream infections. ICU staff outcomes include morale, productivity and job satisfaction (Cummings et al., 2018).…”
Section: Quality Measures In Intensive Care Unitsmentioning
confidence: 99%
“…Important outcome measures include mortality, readmission, patient and family experience, and staff outcomes. Outcome measures in ICUs include mortality, outcomes of infection control, prevention of gastrointestinal bleeding and pressure ulcers, prevalence of sepsis, central line‐associated bloodstream infections (Lee et al., 2019; Pharande et al., 2018), ventilator‐acquired pneumonia (VAP) and catheter‐related bloodstream infections. ICU staff outcomes include morale, productivity and job satisfaction (Cummings et al., 2018).…”
Section: Quality Measures In Intensive Care Unitsmentioning
confidence: 99%
“…It has been confirmed that the introduction of the bundles is associated with a reduction in late-onset systemic infections among infants in the NICU [83,84,85]. The bundles, constructed separately for individual procedures or periods of care, are written locally to better adapt them to the specificities of a unit.…”
Section: Resultsmentioning
confidence: 99%
“…The bundles when applied together, result in substantially greater improvement. For example, activities of the central line bundle, as described by Pharande, include strict hand hygiene, maximal sterile barrier precautions, proper skin antisepsis, aseptic technique, optimal site choice for line insertion, transparent sterile dressing, surveillance, and documentation [85]. According to the authors, implementation of the bundle during a 15-year period resulted in a constant decline in the incidence of LOS and CLABSI in their NICU, in spite of an increase in admissions to the NICU, an increase in central line utilization, and no decrease in the number of high-risk infants.…”
Section: Resultsmentioning
confidence: 99%
“…Central line placement, used for administration of parenteral nutrition and antibiotics, risks the introduction of pathogens to the bloodstream and is the likely cause of many BSIs. As such, increased hygienic practices implemented in hospitals have resulted in a stark decrease in LOS caused by normal skin commensals [7]. However, despite these efforts, LOS rates in neonates remain unchanged among cases caused by gut commensals, suggesting the bacteria are entering the bloodstream through another mechanism [7].…”
Section: Introductionmentioning
confidence: 99%
“…As such, increased hygienic practices implemented in hospitals have resulted in a stark decrease in LOS caused by normal skin commensals [7]. However, despite these efforts, LOS rates in neonates remain unchanged among cases caused by gut commensals, suggesting the bacteria are entering the bloodstream through another mechanism [7].…”
Section: Introductionmentioning
confidence: 99%